From osmotic imbalance to germination arrest: key physiological nodes in the drought-alkaline interaction of alfalfa - Zhang, Yunfei; Hang, Hongtao; Wan, Xiaomei; Guo, Guoling; Li, Chuanting (Frontiers in Plant Science, 2025)
Alfalfa (Medicago sativa L.) is often constrained by factors such as drought and salinity-alkalinity in cultivation. This study aims to investigate the differential response characteristics and physiological-ecological mechanisms of alfalfa during the germination stage under drought, bicarbonate, and drought-salt combined stress. Drought stress was simulated using PEG-6000 (0–20%), and salinity-alkalinity stress was simulated using NaHCO3 (0–30 mM) to conduct germination tests on 12 alfalfa varieties. Based on the semi-inhibitory concentrations of germination and phenotypic indicators of the 12 alfalfa varieties under either drought or bicarbonate stress, drought-salt combined stress was applied. A membership function method was used to comprehensively evaluate the differential responses of the 12 alfalfa varieties to drought and salinity during germination, as well as the physiological-ecological response mechanisms of drought-tolerant, salt-tolerant, and drought-salt sensitive varieties. (1) There were significant differences among varieties in response to single drought or bicarbonate, identifying drought-tolerant varieties WL440HQ and WL363HQ, salt-tolerant variety WL525HQ, drought-sensitive 30°N, and salt-sensitive WL343HQ. Comprehensive evaluation indicated that the strongest and weakest drought and salt-resistant varieties were WL363HQ and WL319HQ, respectively; (2) Drought-salt combined stress exhibited antagonism at low concentrations and synergism at high concentrations; (3) The drought-salt tolerant variety WL363HQ adapted well to the combined stress through mechanisms involving SOD activity and soluble sugars, while the sensitive variety WL319HQ performed poorly. This study provides a scientific basis for elucidating the germination response mechanisms of plants under drought-salt combined stress and offers scientific support for planting in arid and saline-alkaline regions based on the selected drought- and salt-tolerant varieties.